Studying Ni(II) Adsorption of Magnetite/Graphene Oxide/Chitosan Nanocomposite - Luyen T. Tran; Hoang V. Tran; Thu D. Le; Giang L. Bach; Lam D. Tran (Advances in Polymer Technology)
In this paper, Fe3O4/graphene oxide/chitosan (FGC) nanocomposite was synthesized using coprecipitation method for application to removal of nickel ion (Ni(II)) from aqueous solution by adsorption process. To determine residue Ni(II) ions concentration in aqueous solution after adsorption process, we have used UV-Vis spectrophotometric method, which is an effective and exact method for Ni(II) monitoring at low level by using dimethylglyoxime (DMG) as a complex reagent with Ni(II), which has a specific adsorption peak at the wavelength of 550 nm on UV-Vis spectra. A number of factors that influence Ni(II) ions adsorption capacity of FGC nanocomposite such as contact time, adsorption temperature, and adsorbent dosage were investigated. Results showed that the adsorption equilibrium is established after 70 minutes with the adsorbent dosage of 0.01 g.mL−1 at 30°C (the room temperature). The thermodynamic and kinetic parameters of this adsorption including free enthalpy change (∆G0), enthalpy change (∆H0), entropy change (∆S0), and reaction order with respect to Ni(II) ions were also determined. The Ni(II) ions adsorption equilibrium data are fitted well to the Langmuir isotherm and the maximum monolayer capacity (qmax) is 12.24 mg.g−1. Moreover, the FGC adsorbent can be recovered by an external magnet; in addition, it can be regenerated. The reusability of FGC was tested and results showed that 83.08% of removal efficiency was obtained after 3 cycles. The synthesized FGC nanocomposite with many advantages is a promising material for removal of heavy metal ions from aqueous solution to clean up the environment.